2021
DOI: 10.1051/0004-6361/202038500
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the rarest morphologies of the LOFAR Two-metre Sky Survey radio source population with self-organised maps

Abstract: Context. The Low Frequency Array (LOFAR) Two-metre Sky Survey (LoTSS) is a low-frequency radio continuum survey of the Northern sky at an unparalleled resolution and sensitivity. Aims. In order to fully exploit this huge dataset and those produced by the Square Kilometre Array in the next decade, automated methods in machine learning and data-mining will be increasingly essential both for morphological classifications and for identifying optical counterparts to the radio sources. Methods. Using self-organising… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…de Gasperin et al 2019, Morabito et al 2021, efficient distributed processing (Drabent et al 2019 andMechev et al 2018), photometric redshift estimators (Duncan et al 2019) and automated source classification (e.g. Mostert et al 2021 andMingo et al 2019). Excitingly, despite all of these advances, the LOFAR surveys data still retain vast, and largely untapped, potential.…”
Section: Introductionmentioning
confidence: 99%
“…de Gasperin et al 2019, Morabito et al 2021, efficient distributed processing (Drabent et al 2019 andMechev et al 2018), photometric redshift estimators (Duncan et al 2019) and automated source classification (e.g. Mostert et al 2021 andMingo et al 2019). Excitingly, despite all of these advances, the LOFAR surveys data still retain vast, and largely untapped, potential.…”
Section: Introductionmentioning
confidence: 99%
“…Zieba et al 2019;Tajiri et al 2020). A useful extension to this behaviour is that not only are those data which are most similar placed closest together in the final map, but those which are most different are placed furthest apart (Mostert et al 2021). However, an important proviso with the use of the SOM is that far more importance should be given to the relative position of the analysed data compared to its overall distribution, since, as noted by Geach (2012), the randomness of the initial SOM setup results in a different final distribution on each new run, even for precisely the same input data-set.…”
Section: Self-organising Mapsmentioning
confidence: 99%
“…In wider astronomy SOMs have been used for a wide array of analyses, from Photometric Redshift calibration (Geach 2012;Carrasco Kind & Brunner 2014;Wright et al 2020a,b), Radio astronomy (Galvin et al 2020;Mostert et al 2021) and spectroscopic image segmentation (Fustes et al 2013;Schilliro & Romano 2021) to classification of Galaxies (Naim et al 1997;Johnston et al 2021), AGNs (Faisst et al 2019) and unusual quasars (Meusinger et al 2012). Of particular note were the discoveries of Johnston et al (2021) who showed how effective SOMs can be at identifying systematics alongside the main data-groups (in their case in a study of galaxy clustering in the Kilo-Degree Survey), and Khacef et al (2020)'s suggestion that the efficiency of SOMs could be improved for very large data-sets by applying the SOM to extracted features rather than the raw data.…”
Section: Self-organising Mapsmentioning
confidence: 99%
“…A comprehensive review with a performance comparison of different solutions is given by Roscani et al (2020). Denoising tools are usually available within source finding software packages, like PyBDSF (Mostert et al 2021), SoFiA (Serra et al 2015) and AEGEAN (Hancock et al 2012) among the most up-to-date. Also of note are comprehensive and widely adopted software platforms, able to perform most of the previous tasks, like CASA (McMullin et al 2007), AIPS (Greisen 2003), MIRIAD (Sault et al 1995) and ASKAPsoft (Wieringa et al 2020).…”
Section: Introductionmentioning
confidence: 99%